2019
DOI: 10.1016/j.neuroimage.2019.03.072
|View full text |Cite
|
Sign up to set email alerts
|

The brain-derived neurotrophic factor Val66Met genotype does not influence the grey or white matter structures underlying recognition memory

Abstract: A single nucleotide polymorphism (SNP) in the gene coding for brain-derived neurotrophic factor (BDNF) has previously been associated with a reduction in recognition memory performance. While previous findings have highlighted that this SNP contributes to recognition memory, little is known about its influence on subprocesses of recognition, familiarity and recollection. Previous research has reported reduced hippocampal volume and decreased fractional anisotropy in carriers of the Met allele across a range of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
(143 reference statements)
1
4
0
Order By: Relevance
“…Given that other research groups have argued 38 VAL66MET GENOTYPE INFLUENCES RECOGNITION ERPs familiarity to also modulate the LPC, we propose our findings might best be described as reflecting the impact of the Val66Met SNP on general recognition, or potentially on familiarity-related recognition. Importantly, these behavioural and electrophysiological results are reported in the absence of any major structural changes within the brain (see McKay et al, 2019). We, therefore, propose that these results are evidence of a functional influence of the Val66Met SNP on recognition memory.…”
Section: Val66met Genotype Influences Recognition Erpssupporting
confidence: 51%
See 2 more Smart Citations
“…Given that other research groups have argued 38 VAL66MET GENOTYPE INFLUENCES RECOGNITION ERPs familiarity to also modulate the LPC, we propose our findings might best be described as reflecting the impact of the Val66Met SNP on general recognition, or potentially on familiarity-related recognition. Importantly, these behavioural and electrophysiological results are reported in the absence of any major structural changes within the brain (see McKay et al, 2019). We, therefore, propose that these results are evidence of a functional influence of the Val66Met SNP on recognition memory.…”
Section: Val66met Genotype Influences Recognition Erpssupporting
confidence: 51%
“…Genotyped participants were divided into two groups, those with the Val/Val genotype, and those with at least one copy of the Met allele. A subset of sixty-one of the participants that completed the EEG task also participated in an MRI, which has been previously reported (McKay, Moreau, Henare, & Kirk, 2019) . All participants gave informed consent, and this study was approved by the University of Auckland Human Participants Ethics Committee.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third analysis included the smaller regions, accounting for bilateral volumes, yielding 142 outcome measures (Model C). Finally, dMRI measures were included, after taking the average between the left and right side for FA and MD measures, as done previously (McKay et al, 2019). This exploratory approach was conducted previously by at least one other study of vitamin D deficiency and WMI (Moon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…When the interaction of cortical volume with the NIBS effect was considered, the volume of the sensorimotor cortex positively predicted the NIBS effect on MEP changes (Conde et al, 2012). However, this hypothesis lacks reliable information, because the different cortical volumes did not correspond to the same regions (Yang et al, 2012;Jasińska et al, 2017;Shen et al, 2020), and some studies failed to show the genotype-related cortical volume changes (Kim et al, 2015;McKay et al, 2019). Moreover, one study showed that the M1 volume in the Met/Met group was larger than that in the other groups (Jasińska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%